Intracranially recorded ictal direct current shifts may precede high frequency oscillations in human epilepsy. Issue 1 (January 2015) - Kanazawa, Kyoko; Matsumoto, Riki; Imamura, Hisaji; Matsuhashi, Masao; Kikuchi, Takayuki; Kunieda, Takeharu; Mikuni, Nobuhiro; Miyamoto, Susumu; Takahashi, Ryosuke; Ikeda, Akio
Highlights Either ictal direct current shifts or high frequency oscillations were observed in more restricted areas than conventional ictal changes. Both ictal direct current shifts and high-frequency oscillations contributed to delineate the core of tissue generating epileptic seizures. The earlier occurrence of ictal direct current shifts than high frequency oscillations may suggest an active role of glia in seizure generation.